Molecular Mechanisms of Pseudomonas -Assisted Plant Nitrogen Uptake: Opportunities for Modern Agriculture - Sanow, Stefan; Kuang, Weiqi; Schaaf, Gabriel; Huesgen, Pitter; Schurr, Ulrich; Roessner, Ute; Watt, Michelle; Arsova, Borjana (Molecular plant-microbe interactions, 2023)
Pseudomonas spp. make up 1.6% of the bacteria in the soil and are found throughout the world. More than 140 species of this genus have been identified, some beneficial to the plant. Several species in the family Pseudomonadaceae, including Azotobacter vinelandii AvOP, Pseudomonas stutzeri A1501, Pseudomonas stutzeri DSM4166, Pseudomonas szotifigens 6HT33bT, and Pseudomonas sp. strain K1 can fix nitrogen from the air. The genes required for these reactions are organized in a nitrogen fixation island, obtained via horizontal gene transfer from Klebsiella pneumoniae, Pseudomonas stutzeri, and Azotobacter vinelandii. Today, this island is conserved in Pseudomonas spp. from different geographical locations, which, in turn, have evolved to deal with different geo-climatic conditions. Here, we summarize the molecular mechanisms behind Pseudomonas-driven plant growth promotion, with particular focus on improving plant performance at limiting nitrogen (N) and improving plant N content. We describe Pseudomonas-plant interaction strategies in the soil, noting that the mechanisms of denitrification, ammonification, and secondary metabolite signaling are only marginally explored. Plant growth promotion is dependent on the abiotic conditions and differs at sufficient and deficient N. The molecular controls behind different plant responses are not fully elucidated. We suggest that superposition of transcriptome, proteome, and metabolome data and their integration with plant phenotype development through time will help fill these gaps. The aim of this review is to summarize the knowledge behind Pseudomonas-driven nitrogen fixation and to point to possible agricultural solutions. [Formula: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY 4.0 International license .